The Effect of Service Quality and Consumer Satisfaction on Customer Loyalty - Abdul Hakim; Ami Nurhayati; Nyoman Sukmawati (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The research aims to find out whether service quality and customer satisfaction simultaneously or partially have a significant effect on customer loyalty at PT Inti Cakrawala Citra. The type of research used is a quantitative approach. Data was collected using questionnaires, interviews and observation methods. The data analysis technique used was the multiple linear regression test using SPSS Version 26 tools. The sample in this study was 73 respondents. The results of this research show that the variables of service quality and customer satisfaction simultaneously have a significant effect on customer loyalty at PT Inti Cakrawala Citra. The service quality variable partially has a significant effect on customer loyalty at PT Inti Cakrawala Citra. The consumer satisfaction variable partially has a significant effect on customer loyalty at PT Inti Cakrawala Citra.